21st AIAA Aerodynamic Decelerator Systems Technology Conference and Seminar 2011
DOI: 10.2514/6.2011-2557
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of CPAS Flight Testing

Abstract: The Crew Exploration Vehicle Parachute Assembly System (CPAS) is being designed to land the Orion Crew Module (CM) at a safe rate of descent at splashdown via a series of Drogue, Pilot, and Main parachutes. Because Orion is considerably larger and heavier than Apollo, many of the flight test techniques developed during the Apollo program must be modified. The Apollo program had a dedicated C-133 aircraft, which was modified to allow a simple airdrop of "boilerplate" flight test vehicles. However, the CPAS prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…The PTV does not have an active control system (required for controlled subsonic flight). As a result, the PTV cannot achieve the nominal entry deploy conditions using standard LVAD extraction altitudes as a starting point 3 . This limitation is most relevant to the Forward Bay Cover jettison and drogue phases of the CPAS design without loss of control.…”
Section: Figure 1 the Pcdtv And The Ptv Test Articlesmentioning
confidence: 99%
“…The PTV does not have an active control system (required for controlled subsonic flight). As a result, the PTV cannot achieve the nominal entry deploy conditions using standard LVAD extraction altitudes as a starting point 3 . This limitation is most relevant to the Forward Bay Cover jettison and drogue phases of the CPAS design without loss of control.…”
Section: Figure 1 the Pcdtv And The Ptv Test Articlesmentioning
confidence: 99%
“…Other mid-air separation systems have had vehicles with active control systems or vehicle shapes that are more aerodynamically stable than the platform and capsule shapes. 7 Neither the PTV2 nor the CPSS will have an active control system. Fortunately, experience with delayed load transfer extractions has shown that the attitude motion upon extraction is predictable, at least in a qualitative sense.…”
Section: Boilerplate Test Concept Of Operationsmentioning
confidence: 99%
“…However, the method used to deliver the Apollo boilerplate capsule to the test condition is infeasible due to the size of the Orion capsule and the available airframes. 7 CPAS has investigated an alternative technique that uses a modified Low Velocity Aerial Delivery (LVAD) system to extract a truncated boilerplate from a C-17 and deliver it to the test condition. The concept of operations for this technique will be described.…”
Section: Introductionmentioning
confidence: 99%
“…The primary method of testing is through Low-Velocity Aerial Delivery (LVAD) drop tests. 1 During the current Engineering Development Unit (EDU) phase of testing, speciallydesigned test vehicles are extracted from an aircraft at 25,000 ft-Mean Sea Level (MSL), and a programmer parachute is used to achieve the desired conditions at Drogue parachute deployment. One of the primary test vehicles is the Parachute Test Vehicle (PTV).…”
Section: Introductionmentioning
confidence: 99%